Pemerintah dan Korban Kekerasan Dalam Keluarga Islam di Indonesia: Perlindungan Hukum, Peran dan Pemenuhan Hak - Suwanti; Syamsudin; Baehaqi (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
Family violence poses a significant threat to the well-being and human rights of individuals, particularly children. This article examines the initiatives undertaken by the Boyolali Government's Office of Population Control, Family Planning, Women's Empowerment, and Child Protection (DP2KBP3A) to safeguard victims of violence within Islamic households. Utilizing a legal framework, the study evaluates the role and the extent to which the rights of victims of familial violence are met. Through the analysis of secondary data and qualitative assessments, this article sheds light on the strategies, policies, and programs implemented by DP2KBP3A Boyolali to ensure effective legal protection for victims of violence within Islamic families. The discussion concludes that such protection is paramount and encompasses various forms of violence, including emotional, verbal, sexual, and physical abuse, which are addressed in Law No. 35 of 2014 and other relevant regulations. The repercussions of violence against children are severe, posing risks to their physical and mental health and diminishing their quality of life. Poor parenting practices, including child abuse, can profoundly impact a child's development and well-being. In response, DP2KBP3A Boyolali District offers complaint, prevention, and rehabilitation services spanning legal assistance, health assessments, and counseling. These endeavors are crucial in shielding children from violence and fostering a nurturing family environment conducive to their growth. The insights gleaned from this study offer valuable guidance for enhancing the legal protection of family violence victims and underscore the pivotal role of governmental agencies in upholding their rights.